Mastering ROS for Robotics Programming - Third Edition - Joseph, Lentin; Cacace, Jonathan (Packt Publishing, 2021)
Design, build, and simulate complex robots using the Robot Operating System Key Features Become proficient in ROS programming using C++ with this comprehensive guide Build complex robot applications using the ROS Noetic Ninjemys release to interface robot manipulators with mobile robots Learn to interact with aerial robots using ROS Book Description The Robot Operating System (ROS) is a software framework used for programming complex robots. ROS enables you to develop software for building complex robots without writing code from scratch, saving valuable development time. Mastering ROS for Robotics Programming provides complete coverage of the advanced concepts using easy-to-understand, practical examples and step-by-step explanations of essential concepts that you can apply to your ROS robotics projects. The book begins by helping you get to grips with the basic concepts necessary for programming robots with ROS. You'll then discover how to develop a robot simulation, as well as an actual robot, and understand how to apply high-level capabilities such as navigation and manipulation from scratch. As you advance, you'll learn how to create ROS controllers and plugins and explore ROS's industrial applications and how it interacts with aerial robots. Finally, you'll discover best practices and methods for working with ROS efficiently. By the end of this ROS book, you'll have learned how to create various applications in ROS and build your first ROS robot. What you will learn Create a robot model with a 7-DOF robotic arm and a differential wheeled mobile robot Work with Gazebo, CoppeliaSim, and Webots robotic simulators Implement autonomous navigation in differential drive robots using SLAM and AMCL packages Interact with and simulate aerial robots using ROS Explore ROS pluginlib, ROS nodelets, and Gazebo plugins Interface I/O boards such as Arduino, robot sensors, and high-end actuators Simulate and perform motion planning for an ABB robot and a universal arm using ROS-Industrial Work with the motion planning features of a 7-DOF arm using MoveIt Who this book is for If you are a robotics graduate, robotics researcher, or robotics software professional looking to work with ROS, this book is for you. Programmers who want to explore the advanced features of ROS will also find this book useful. Basic knowledge of ROS, GNU/Linux, and C++ programming concepts is necessary to get started with this book.
Online resource; Title from title page (viewed October 28, 2021)
Keywords: Robotics; Operating systems (Computers); Robotique; Systèmes d'exploitation (Ordinateurs); operating systems